Perceptions of students and entrepreneurs on service-learning in costs and marketing - Ganga-Contreras, Francisco; Guiñez-Cabrera, Nataly; Rodríguez-Quezada, Estela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The objective of this study is to present the appreciation of students and microentrepreneurs, regarding the application of the service-learning methodology. A self-efficacy survey applied to students and a satisfaction survey to microentrepreneurs who received the advice were used. It was found that the implemented service-learning experience had a positive impact on students in their teaching-learning process, developing professional and social skills. The microentrepreneurs highlighted that the proposed expectations were met, and among the aspects to be improved they pointed out: the time allocated, the organization, and the scope of the advice, they would have liked to develop something with greater impact.